A scalar implicature-based approach to Neg-raising - Romoli, Jacopo (Proceedings of Sinn und Bedeutung, 2019)
In this paper, I give an analysis of neg-raising inferences as scalar implicatures. The main motivation for this account as opposed to a presupposition-based approach (Bartsch 1973 and Gajewski 2005, 2007) comes from the differences between presuppositions and neg-raising inferences, noticed by Gajewski (2005, 2007) and Homer (2012). In response to this issue, Gajewski (2007) argues that neg-raising predicates are soft presuppositional triggers and adopts the account of how their presuppositions arise by Abusch (2002, 2010). However, I argue that there is a difference between soft triggers and neg-raising predicates in their behavior in embeddings; a difference that is straightforwardly accounted for in the present approach. Furthermore, by adopting Abusch’s (2010) account of soft triggers, Gajewski (2007) inherits the assumptions of a pragmatic principle of disjunctive closure and of a non-standard interaction between semantics and pragmatics - assumptions that are not needed by the present proposal, which is just based on a regular theory of scalar implicatures.